OPTIMAL AIRCRAFT CONTROL SYNTHESIS BASED ON THE EQUATIONS OF NON-LINEAR DYNAMICS - V. F. Dil; V. N. Sizykh (Научный вестник МГТУ ГА, 2017)
The article considers the technique of the synthesis of non-linear aircraft control systems by flight optimization us- ing inverse dynamics problems. To synthesize control algorithms a non-linear model of aircraft flight and trajectory movement is used. The authors define method stages of flying level synthesis which include: selection of aircraft reference movements in accordance with three degrees of freedom, structuring the control algorithms and their parameters, defining the proximity of current and reference movements by means of a quadratic functional and further extremum-minimum movement organization by the gradient method. Through the optimized parameters of flying level the direct dynamics problem of trajectory level control of the aircraft spatial movement is solved. The basis for calculating the aircraft trajecto- ry parameters is a non-linear model of the trajectory movement for which flying level output parameters serve as input data. The trajectory level output parameters are defined by numerical integration of input signals considering aircraft dynamic blow coefficients. The structure diagram of aircraft spatial movement control organization is developed. The flight contour functioning is examined using numerical modeling in MathCad and Paskal programs. Reference parameters were determined by Paskal simulation modeling according to the reaction of a non-linear aircraft model to the “bounces” of aerody- namical flight controls. It is shown that the spatial control problem is optimal in terms of input control realization. Besides, in comparison with [9] it is possible to state that due to energy reversibility of rotational and progressive movements only the content of direct and inversed problems of dynamics changes.